2010
DOI: 10.1007/s00125-010-1732-x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte nuclear factor (HNF)-4α-driven epigenetic silencing of the human PED gene

Abstract: These results show that HNF-4alpha serves as a scaffold protein for histone deacetylase activities, thereby inhibiting liver expression of genes including PED. Dysregulation of these mechanisms may lead to upregulation of the PED gene in type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…In the TCF4-HNF4a complex, HNF4a might mimic the Wnt turned-off status. In support of the last two mechanisms, published reports indicated that HNF4a associates with HDAC-containing SMRT complex to repress gene expression (Ruse et al, 2002;Ungaro et al, 2010). In this scenario, the TCF4-HNF4a complex may recruit the co-repressors through HNF4a or HNF4a and TCF4 together.…”
Section: Discussionmentioning
confidence: 85%
“…In the TCF4-HNF4a complex, HNF4a might mimic the Wnt turned-off status. In support of the last two mechanisms, published reports indicated that HNF4a associates with HDAC-containing SMRT complex to repress gene expression (Ruse et al, 2002;Ungaro et al, 2010). In this scenario, the TCF4-HNF4a complex may recruit the co-repressors through HNF4a or HNF4a and TCF4 together.…”
Section: Discussionmentioning
confidence: 85%
“…Mycoplasma contamination was not detected in L6 cells. Trichostatin A treatment and 2-deoxyglucose (2-DG) uptake were performed as previously reported [24,25].…”
Section: Methodsmentioning
confidence: 99%
“…Chromatin immunoprecipitation and re-chromatin immunoprecipitation assay procedures The chromatin immunoprecipitation (ChIP) assay was performed as described previously [24]. DNA fragments were recovered and subjected to PCR using the primer sequences described in ESM Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Ungaro et al (34) provided some of the first evidence that HNF4␣ may function as a negative transcriptional regulator. Their data support the hypothesis that HNF4␣ negatively regulates expression of the preimplantation embryonic development (PED) gene in the liver.…”
mentioning
confidence: 99%